2016
DOI: 10.1002/jrs.4985
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of urinary stones as studied by means of multimodal nonlinear optical imaging

Abstract: Tracing aetiology and pathogenesis of urinary stone disease is of great importance in order to prescribe appropriate treatment and prevent recurrences. For this purpose, morphological examination combined with determination of chemical composition of urinary stones is fundamental. In this work, we have evaluated the potential of multimodal nonlinear optical imaging for investigation of (micro)structure and chemical composition of human urinary stones. The method provides high‐resolution multimodal images of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
3
7
0
3
Order By: Relevance
“…Pucetaite et al determined the microstructure of urinary stones by means of multimodal nonlinear optical imaging. Their results showed that multimodal nonlinear optical imaging can provide relevant information about growth processes of urinary stones and deliver useful insights into the etiology and pathogenesis of urolithiasis . Schlabritz‐Loutsevitch et al used Raman spectroscopy as a novel method in placental research.…”
Section: Biosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pucetaite et al determined the microstructure of urinary stones by means of multimodal nonlinear optical imaging. Their results showed that multimodal nonlinear optical imaging can provide relevant information about growth processes of urinary stones and deliver useful insights into the etiology and pathogenesis of urolithiasis . Schlabritz‐Loutsevitch et al used Raman spectroscopy as a novel method in placental research.…”
Section: Biosciencesmentioning
confidence: 99%
“…Their results showed that multimodal nonlinear optical imaging can provide relevant information about growth processes of urinary stones and deliver useful insights into the etiology and pathogenesis of urolithiasis. [71] Schlabritz-Loutsevitch et al used Raman spectroscopy as a novel method in placental research. Their report is the first attempt to identify the Raman fingerprint associated with placental hypoxia.…”
Section: Medical and Biomedical Applications Tissues Plants And mentioning
confidence: 99%
“…Φασµατοσκοπία Ενεργής Διασποράς Ακτίνων -Χ ή Energy Dispersive X -Ray Spectroscopy [13], [183], [184], [205], [208], [209]. Γενικά, η µικροσκοπία παρέχει πληροφορίες για τη µορφολογία της επιφανείας των δειγµάτων, το χρώµα (πλην των ηλεκτρονιακών µικροσκοπίων) και τη βασική σύνθεση των λίθων.…”
Section: Scanning Electron Microscopy (Sem)unclassified
“…Γενικά, η µικροσκοπία παρέχει πληροφορίες για τη µορφολογία της επιφανείας των δειγµάτων, το χρώµα (πλην των ηλεκτρονιακών µικροσκοπίων) και τη βασική σύνθεση των λίθων. Τα δύο πιο κοινά µικροσκόπια είναι τα οπτικά και τα ηλεκτρονιακά µικροσκόπια σάρωσης, τα οποία όµως έχουν σηµαντικές διαφορές και στο επίπεδο µεγέθυνσης αλλά και στο κόστος χρήσης [9], [183], [205], [208]- [210] .…”
Section: Scanning Electron Microscopy (Sem)unclassified
See 1 more Smart Citation